The Evolution of Mathematical Representation Research in Realistic Mathematics Education: A PRISMA-Guided Bibliometric Review - Putri Juliyanti; Arif Abdul Haqq; Muhammad Azam (International Journal of Contemporary Studies in Education (IJ-CSE), 2026)
Purpose – Mathematical representation is a core component of Realistic Mathematics Education (RME), enabling learners to construct mathematical meaning through multiple representations. Despite the growing body of research, existing reviews largely emphasize instructional effectiveness or bibliometric trends without explaining the field's intellectual evolution. This study mapped the evolution of mathematical representation research within RME by examining its research landscape, knowledge diffusion, intellectual structure, thematic development, and future directions. Methodology – An integrated Systematic Literature Review and bibliometric analysis was conducted following the PRISMA protocol. Thirty-eight English-language journal articles indexed in Scopus were analysed using VOSviewer through publication trend analysis, collaboration networks, keyword co-occurrence, overlay and density visualisations, and bibliographic coupling. Findings – Research has progressed through four developmental phases: Foundation, Expansion, Diversification, and Integration. The findings reveal global knowledge diffusion from the Netherlands as the theoretical origin to Indonesia as the principal site of contextual adaptation, with Malaysia serving as a key regional collaborator. Four interconnected intellectual domains emerged: instructional design, mathematical representation, assessment, and educational technology. Emerging research frontiers include longitudinal representational development, adaptive assessment, artificial intelligence, teacher professional learning, and cross-cultural implementation. Novelty – This study proposes a theory-oriented bibliometric synthesis that integrates research trends, knowledge diffusion, intellectual structures, thematic evolution, and research frontiers into a unified conceptual framework. Significance – The findings provide an evidence-based foundation for theory development, research prioritisation, and instructional innovation, advancing mathematical representation as a central construct in contemporary mathematics education.